Additional table for easier access to ankle fracture: A retrospective study of traditional positioning versus modified positioning. Issue 45 (6th November 2020) - Liu, Bo; Jin, Rui; Rai, Saroj; Liu, Ruikang; Hong, Pan
Abstract : Abstract: An interest in the fixation of posterior malleolus via the posterolateral approach has gained popularity recently. Most surgeons choose prone or lateral position during the surgery, and this study proposes an additional radiolucent table for easier access to the posterolateral anatomic structure of ankle joint, and compares it with traditional positioning. From September 2014 to September 2018, 21 patients with trimalleolar fractures and 28 patients with posterior malleolus and fibular fractures receiving open reduction and internal fixation (ORIF) using the posterolateral approach with the utilization of an additional radiolucent table were included in Additional Table group. Patients of matched sex, age, and injury type using the same surgical approach with the traditional positioning were selected from the hospital database and included in the Traditional group. Baseline information and clinical parameters were recorded. No significant differences existed concerning age, sex, or operative side between the 2 groups in patients with trimalleolar fractures. The time for positioning was significantly longer in the Traditional group (20.5 ± 6.45 minutes) than the Additional Table group (12 ± 3.5 minutes) ( P < .001). Besides, the operative time in the Traditional group (75.28 ± 5.45 minutes) was significantly longer than the Additional Table group (58 ± 5.95 minutes) ( P < .001). There was no case of nonunion and malunion in both groups. At 12-month follow-up, the American Orthopedic Foot and Ankle Society Scale (AOFAS) score showed no significant difference between the 2 groups ( P = .46). In patients with fibular fracture and posterior malleolus fracture, no significant differences existed concerning age, sex, operative side between the 2 groups. The time for positioning was significantly longer in the Traditional group (16.5 ± 3.45 minutes) than the Additional Table group (11 ± 3.5 minutes) ( P < .001). Besides, the operative time in the Traditional group (55.28 ± 8.45 minutes) was significantly longer than the Additional Table group (44 ± 7.95 minutes) ( P < .001). There was no case of nonunion and malunion in both groups. At the 12-month follow-up, the AOFAS score showed no significant difference between the 2 groups ( P = .26). The novel positioning with an additional table is an excellent choice for trimalleolar fracture, posterior malleolus fracture, with/without distal fibular fracture.